TEACHERS' EFFORTS TO INCREASE THE LEARNING MOTIVATION OF CHILDREN AGED 5-6 YEARS THROUGH TRADITIONAL CUBLAK-CUBLAK SUWENG GAMES - Kangiden, Farida Ariyani; Mustahidin, Arip Arizal; Lesiani, Lesi (Waniambey: Journal of Islamic Education, 2025)
Motivation to learn is an important thing that must be built from an early age. Teachers are one of the motivators at school who must be able to build children's interest in learning.  Play is one of the ways children gain knowledge, in other words, playing for children is learning. So the learning given to children must be through play, such as the traditional game cublak-cublak suweng conducted by teachers in Cilegon City. The traditional game is given to children aged 5-6 years in an effort to increase children's learning motivation which is still low. The research was conducted using the John Elliot model of classroom action research consisting of 2 cycles, where each cycle consists of planning, implementation, observation and reflection stages. The results showed that children's learning motivation increased from pre-cycle to cycle 2. Children showed a high attitude of curiosity, interest in playing again, feeling pleasure while playing, and knowledge as well as commands conveyed by the teacher through traditional games can be accepted and carried out by children very well. In other words, the traditional game cublak-cublak suweng is effective and successful in increasing the learning motivation of children aged 5-6 years.